Fabry Disease: angiokeratoma, biomarker, and the effect of enzyme replacement therapy on kidney function - Ries, Markus; Schiffmann, Raphael (Archives of dermatology, 2005)
With great interest we read the editorial “Fabry Disease: More Than Angiokeratomas” by Möhrenschlager and colleagues. We concur with the authors that it would b
Gesehen am 16.05.2019